2016
DOI: 10.1016/j.ijgo.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Overall and abortion‐related maternal mortality rates in Uruguay over the past 25 years and their association with policies and actions aimed at protecting women's rights

Abstract: Objective: To evaluate changes in maternal mortality rates in Uruguay over the past 25 years, as well as their distribution by cause, and their temporal relationship with social changes and Human Development Index (HDI) indicators. Methods: Data on maternal mortality obtained directly from the Uruguayan Ministry of Public Health for the 2001 to 2015 period were analyzed together with data from the United Nations Inter-Agency Group for Child Mortality Estimation for the 1990 to 2015 period. The swiftness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
0
21
0
2
Order By: Relevance
“…This model was originally developed to curtail the spread of HIV/AIDS through exchange of used syringes for new ones in a community in which there was a high prevalence of sharing used syringes. It was reconceptualized in Uruguay to prevent unsafe abortion—also referred to as the Uruguay Model …”
Section: The Harm Reduction Model: Laws Policies and Ethics For Impmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was originally developed to curtail the spread of HIV/AIDS through exchange of used syringes for new ones in a community in which there was a high prevalence of sharing used syringes. It was reconceptualized in Uruguay to prevent unsafe abortion—also referred to as the Uruguay Model …”
Section: The Harm Reduction Model: Laws Policies and Ethics For Impmentioning
confidence: 99%
“…It was reconceptualized in Uruguay to prevent unsafe abortion-also referred to as the Uruguay Model. 7,11 In Uruguay, the law provided very few legal options for abortion and even then, access to services was deterred by lengthy and tedious bureaucratic processes. This was compounded by stigmatizing of applicants by health workers who lacked the will to provide services.…”
Section: The Harm Reduction Model: Laws Policies and Ethics For Imentioning
confidence: 99%
“…While monitoring and evaluation are standard cornerstones for assessing programmatic efficiency and effectiveness, they proved particularly useful in assuaging fears about these new programs. In countries as different as Ghana and Portugal, data demonstrated the rapid decline in abortion associated death that followed availability of safe procedures . While many complained that data were overly aggregated or problematically coded, precluding fine‐tuned analysis, interviewees also reported that they learned from these data how to constructively modify the program, and had been able to refute incorrect stereotypes about characteristics of those seeking abortion.…”
Section: Facilitationmentioning
confidence: 99%
“…While abortions remained illegal and could not be obtained within the health system, this approach gave some legitimacy to women's decision to terminate a pregnancy . It also brought women facing unplanned pregnancies closer to the health system, and reduced abortion‐related morbidity and mortality . In 2004, this model was adopted as an official policy of the Ministry of Health, allowing it to be scaled up to other hospitals throughout the country .…”
Section: Contextmentioning
confidence: 99%
“…7 It also brought women facing unplanned pregnancies closer to the health system, and reduced abortion-related morbidity and mortality. 8 In 2004, this model was adopted as an official policy of the Ministry of Health, allowing it to be scaled up to other hospitals throughout the country. 6 Meanwhile, civil society advocacy during the country's first left-wing coalition government led to Parliamentary approval in 2008 of a bill on sexual and reproductive health, including the decriminalization of abortion.…”
Section: Contextmentioning
confidence: 99%